Cyclitol galactosides in low-raffinose, low-stachyose soybean embryos after feeding d-chiro-inositol, myo-inositol or d-pinitol. Issue 2 (25th February 2013) - Obendorf, Ralph L.; Sensenig, Elizabeth M.; Byrt, Erin M.; Owczarczyk, Anna B.; Ohashi, Minori; Schnebly, Steven R.
Abstract: Sucrose, raffinose and stachyose accumulate as stored soluble carbohydrates in embryos during soybean [ Glycine max L. (Merrill)] seed development and maturation. Raffinose and stachyose in soybean feed products are not digested by humans, chickens or pigs, resulting in flatulence and reduced nutritional value. Soybean lines selected for low raffinose and low stachyose (LRS) or low raffinose, low stachyose and low phytin (LRSP1, LRSP2) concentrations in mature seeds were compared to a CHECK line with normal raffinose, stachyose and phytin. To determine whether increasing the supply of free cyclitols to immature embryos of these lines results in increased accumulation of galactosyl cyclitols, isolated immature embryos free of maternal tissues were fed solutions containing eitherd - chiro -inositol, myo -inositol ord -pinitol, or a control solution without cyclitols, for 24 h. Embryos were precociously matured by slow drying for 14 d with daily transfers to stepwise lower relative humidities. Soluble carbohydrates were extracted from axis and cotyledon tissues of mature, dry embryos and analysed by high-resolution gas chromatography. Axis and cotyledons from LRS, LRSP1 and LRSP2 embryos had low concentrations of stachyose compared to CHECK embryos after feeding a control solution without cyclitols. Feedingd - chiro -inositol to isolated embryos increased fagopyritol B1 accumulation in embryos of all lines. Feeding myo -inositol increased stachyose accumulation in LRSP1 and LRSP2 cotyledons. Feedingd -pinitol increased freed -pinitol in cotyledons of all lines but increased galactopinitol A and galactopinitol B only in LRS cotyledons. Supplying additionald - chiro -inositol to immature embryos can enhance accumulation of fagopyritol B1 in mature embryos of low-raffinose and low-stachyose or low-raffinose, low-stachyose and low-phytin soybeans.